Is a rise in intracellular concentration of free calcium necessary or sufficient for stimulated cytoskeletal-associated actin? (The Rockefeller University Press, 1986)
The addition of the calcium ionophore A23187 to rabbit neutrophils increases the amount of actin associated with the cytoskeleton regardless of the presence or absence of calcium in the incubation medium. In the presence of extracellular calcium, the effect of A23187 is biphasic with respect to concentration. The action of the ionophore is rapid, transient, and is inhibited by pertussis toxin, hyperosmolarity, and quinacrine. On the other hand, the addition of pertussis toxin or hyperosmolarity has small if any, effect on the rise in intracellular calcium produced by A23187. While quinacrine does not affect the fMet-Leu-Phe-induced increase in cytoskeletal actin and the polyphosphoinositide turnover, its addition inhibits completely the stimulated increase in Ca-influx produced by the same stimulus. The results presented here suggest that a rise in the intracellular concentration of free calcium is neither necessary nor sufficient for the stimulated increase in cytoskeletal-associated actin. A possible relationship between the lipid remodeling stimulated by chemoattractants and the increased cytoskeletal actin is discussed.